2011
DOI: 10.1523/jneurosci.2246-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic Interrogation of Dopaminergic Modulation of the Multiple Phases of Reward-Seeking Behavior

Abstract: Phasic activation of dopaminergic neurons is associated with reward-predicting cues and supports learning during behavioral adaptation. While non-contingent activation of dopaminergic neurons in the ventral tegmental are (VTA) is sufficient for passive behavioral conditioning, it remains unknown whether the phasic dopaminergic signal is truly reinforcing. In this study, we first targeted the expression of channelrhodopsin-2 (ChR2) to dopaminergic neurons of the VTA and optimized optogenetically-evoked dopamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
265
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(285 citation statements)
references
References 50 publications
16
265
1
3
Order By: Relevance
“…It is interesting to note that a similar attenuation of effect between optical and electrical stimulation was observed by others in VTA DA-mediated reward behaviors. Optical activation of VTA DA neurons was insufficient to produce self-stimulation reward seen with electrical stimulation (45, 46) but instead required a pairing of a food-seeking behavior to see a significant effect (47).…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that a similar attenuation of effect between optical and electrical stimulation was observed by others in VTA DA-mediated reward behaviors. Optical activation of VTA DA neurons was insufficient to produce self-stimulation reward seen with electrical stimulation (45, 46) but instead required a pairing of a food-seeking behavior to see a significant effect (47).…”
Section: Discussionmentioning
confidence: 99%
“…However, roles of DA neurons in affective processes may be more complicated. Optogenetic stimulation of VTA DA neurons during mild social stress potentiates subsequent induction of depression-like behavior (Chaudhury et al, 2013). Thus, activity of DA neurons may interact with ongoing environmental conditions in subsequent behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, animals intracranially self-administer DAergic drugs into the projection regions of VTA DA neurons (Ikemoto, 2007). Moreover, optogenetic studies showed that the excitation of VTA DA neurons induces conditioned place preference in mice , and mice and rats learn instrumental responding to excite VTA DA neurons (i.e., intracranial self-stimulation, ICSS; Adamantidis et al, 2011;Witten et al, 2011;Kim et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…Precise patterns of phasic photostimulation of these cells, which had previously been shown to evoke maximal levels of downstream DA release (Adamantidis et al 2011), significantly increased the amount of time mice spent investigating a novel conspecific. This effect was blocked by DA receptor antagonism (although no genetic targeting strategy resolves cell types with complete specificity, these results confirmed DA dependence of the behavioral result, supporting prior immunostaining-based validation of this targeting methodology; Tsai et al 2009).…”
Section: A Circuit-based Approach To Social Motivationmentioning
confidence: 95%